An integrated approach to optimize moving average rules in the EUA futures market based on particle swarm optimization and genetic algorithms. (1st January 2017) - Liu, Xiaojia; An, Haizhong; Wang, Lijun; Jia, Xiaoliang
Highlights: We proposed an integrated approach to optimize trading rules in EUA futures market. Adaptive moving average rules with different weights are used to make decision. The integrated rule is adjusted dynamically with PSO and genetic algorithms. Our results show generated trading rules can adapt price changes and make profits. This approach is helpful for traders in choosing trading rules and evading risks. Abstract: Climate change is a big challenge facing global community in 21st century. The carbon emission futures markets has been treated as a key tool to combat climate change cost-effectively. Making profits from futures trading is the fundamental incentive mechanism to keep this market run sustainably and effectively, while few technique analysis research on this topic has been done in the energy finance field. This paper contributes to the literature by proposing an integrated moving average rule for the European Union Allowance (EUA) futures market and designing an approach to optimize the weights of rules based on Particle Swarm Optimization (PSO) and Genetic Algorithms (GAs). The similarity of trading rules designed here is used to select base rules. An integrated approach based on PSO and GAs is proposed to identify the optimal weights group for the selected base rules. A group of Adaptive Moving Average trading rules with different weights constitutes an integrated trading rule. Experiments using the EUA futures market price were conducted. The results show that: (1) our model is profitable in the EUA future market with the proper parameter except the case that prices fluctuate significantly; (2) the adjustment cycle of 5 days is more useful than 20 days or 50 days; (3) the algorithm achieves the best performance at the 0.78 similarity threshold; (4) the rule with the short period of 150 days and the long period of 200 days is a useful building block for a successive rule set. This approach is a useful reference to the practical investments in EUA futures market.